Mediating effect of enterprise risk management implementation on operational excellence in the oil and gas industry: the case of Nigeria - Muazu, Muazu Hassan (2020)
The rising cost of production, risk, environmental concerns and desire to perform, made oil and gas companies adoptedoperational excellence strategy to remedy the situation. In recent time, incidences on safety and health, the cost of exploration, and ageing facility risks in the Nigerian oil and gas industry are rising. The situation if not checked could lead to a continued decline in oil production, revenue,economicperformance and the aspiration of the country to becoming a regional economic force and one of the world’sbest economies will be unrealistic. It is as a result of this development that this study investigatedthe mediating effect of enterprise risk management implementation on the relationship between enterprise risk management determinants and operational excellence in the Nigerian oil and gas sector. The study employed a quantitive survey approach, where seven oil and gas companies were chosen purposively for the research and 179 managers and engineers were surveyed,and data were collected via a closed-ended questionnaire. SPSS 23 was used for the preliminary data analysis,and smart PLS-SEM 3.0 was used for the final analysis. The result showed that regulatory framework, firm characteristics, staff capacity and information technology as independent variables had a significant relationship with operational excellence. Enterprise risk management implementation was found to have a significant relationship with operational excellence and also mediates its relationship with firm characteristics and staff capacity.The study findings substantiate the importance of enterprise risk management implementation in operational excellence in the oil and gas sector.The outcome of the research also indicated a theoretical contribution to the body of knowledge of enterprise risk management implementation as well as operational excellence. It also showed practical improvement in the operations of oil and gas sector as regards risk management and operational excellence in the Nigerian oil and gas sector, specifically the Nigerian National Petroleum Corporation.